PENGARUH METODE PEMBERIAN RANSUM PADA SIANG DAN MALAM HARI TERHADAP PERFORMA AYAM JANTAN TIPE MEDIUM DI KANDANG POSTAL - Ryan Nastiansyah; Syahrio Tantalo; Khaira Nova; Rr Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to determine the effect of the percentage of ration during the day and night on the performance of medium type roosters in postal cages. This research was conducted in August- October 2018 in a postal cage, Integrated Laboratory, Faculty of Agriculture, University of Lampung. The experiment was designed in a Completely Randomized Design (CRD) with 3 treatments, namely giving ration 30% at day and 70% at night ration (R1), 50% at day and 50% at night (R2), and 70% at day and 30% at night (R3). All treatments were repeated six times with each replication consisting of 8 chickens, so that the total experimental chickens were 144 chickens. The material used in this study was 2 weeks old of Lohman strain chicken. The results showed a significant effect (P<0.05) between the percentage of giving ration at day and night on ration consumption, but no significant effect (P>0.05) on body weight gain, feed conversion, and income over feed cost ( IOFC). The result also showed that giving ration 30% during the day and 70% at night was the best proportion for feed consumption. Keywords: Medium type rooster, Postal cage, Night, Ration, Day